Extortion in Mexico - Requenes, J. Isabel García (Seven Editora, 2024)
Extortion has become normalized, to such a degree that it is already part of Mexican culture. In Mexico there is an extorted society.When the extortionist obtains a benefit, money, property, or services by coercing or threatening through physical violence, property destruction, or personal injury, extortion becomes theft.Extortion has become an easy and quick source of financing for organized crime structures, governments and political organizations, including political parties, since it is highly profitable and generates fewer material, economic and human losses."The intuition that only organized crime extorts through violence, kidnapping or threats is false, it also does so through the collection of fees and dues. And it is not only organized crime, but the government itself and its institutions, as well as private companies that are also part of this harmful practice. It all begins, however, in the individual sphere where extortion has become common in everyday life. Accepting illegitimate payment for parking in a public space or being subjected to having your car scratched? Paying for garbage to be collected or putting up with it being left and accumulating on the street? Pay an official to do the procedure quickly or wait weeks or even months? To pay weekly or monthly dues to criminal groups or to be a victim of violent threats? Offering a juicy tip as a mechanism to gain access to a privilege to which one is not entitled?" (De la Calle, 2020)In general, there are two types of extortion, telephone extortion, which is one of the most common crimes and the one that most worries the public security authorities in Mexico, many of them are committed from inside prisons, and face-to-face extortion, which is when the extortionist appears directly at the workplace identifying himself as a member of a criminal organization to charge for the security service or only so as not to do harm, so he threatens to deprive a family member or the victim himself of his life or damage the establishment. This type of extortion is the least investigated because it requires a person to report this crime.The crime of extortion has a 97.4% black figure, that is, it is not reported to the state prosecutors' offices or prosecutors' offices for fear of reprisals from criminals dedicated to extortion or if the authority is involved.Most people, not having enough resources to file a complaint against the crime of extortion, prefer to make a payment, a gift or a moche to a corrupt official or a criminal, since the cost can be much higher than that implied by the initial threat: lawyers, paperwork, etc.  risks and wasted time. DOI:https://doi.org/10.56238/sevened2024.010-057